Exploring Generation Z's Preferences for Halal Cosmetics in the Context of Halal Lifestyle - Utami, Bayu (Riwayat: Educational Journal of History and Humanities, 2025)
This research article aims to explore the preferences of Generation Z towards halal cosmetics in the context of halal lifestyle, using a qualitative approach that is relevant to the development of research in the last five years. Generation Z, as a group of consumers who are critical and aware of ethical values, is the main concern in this study. The data was collected through in-depth interviews with Generation Z respondents who have an interest in halal cosmetics, as well as analysis of documents related to halal lifestyle trends. The study found that Generation Z's preference for halal cosmetics is not only based on the halal aspect of the product, but also includes the values of sustainability, transparency, and production ethics. In addition, social media and digital influences are significant factors in shaping their perceptions and purchasing decisions. This study makes an important contribution to the halal cosmetics industry in understanding the needs and expectations of Generation Z consumers, as well as supporting the development of marketing strategies that are in line with the modern halal lifestyle. The findings also emphasize the need for product innovation that not only complies with halal standards, but also considers aspects of sustainability and ethical values that are relevant to today's consumer preferences.